I'm reading the following book: http://www.cs.princeton.edu/courses/archive/spring10/cos433/mathcs.pdf.
In page 26, they attempt to prove the following theorem using Induction:
For all n∈N:
1+2+⋯+n=n(n+1)2
In order to prove the theorem we need to prove the following statements:
- P(0) is true.
- For all n∈N, P(n) implies P(n+1).
Proving the first one is easy:
P(0)=0=0∗(0+1)/2
=0=0∗1/2
=0=0/2
=0=0
In order to prove the second, they state the following:
1+2+⋯+n+(n+1)=n(n+1)2+(n+1)
=(n+1)(n+2)2
I don't understand how they get from (1) to (2) and how that proves that proves that for all n∈N, P(n) implies P(n+1) is true.
I'm clearly missing something in the process. Can someone clear the fog for me?
Answer
Just do the math.
n(n+1)2+(n+1)=n(n+1)+2(n+1)2=(n+2)(n+1)2
For your second problem, note that you proved that 1+2+…+n+(n+1)=(n+2)(n+1)2.
The initial statement is 1+2+…+k=k(k+1)2, with another letter. If you do k=n+1 you will get 1+2+…+(n+1)=(n+1)((n+1)+1)2=(n+2)(n+1)2, and that is what you just proved.
No comments:
Post a Comment